Clinically Relevant Epithelial Lining Fluid Concentrations of Meropenem with Ciprofloxacin Provide Synergistic Killing and Resistance Suppression of Hypermutable Pseudomonas aeruginosa in a Dynamic Biofilm Model - Bilal, Hajira (Antimicrob Agents Chemother, 2020)
Treatment of exacerbations of chronic Pseudomonas aeruginosa infections in patients with cystic fibrosis (CF) is highly challenging due to hypermutability, biofilm formation, and an increased risk of resistance emergence. We evaluated the impact of ciprofloxacin and meropenem as monotherapy and in combination in the dynamic in vitro CDC biofilm reactor (CBR). Two hypermutable P. aeruginosa strains, PAOΔmutS (MIC of ciprofloxacin [MIC(ciprofloxacin)], 0.25 mg/liter; MIC(meropenem), 2 mg/liter) and CW44 (MIC(ciprofloxacin), 0.5 mg/liter; MIC(meropenem), 4 mg/liter), were investigated for 120 h. Concentration-time profiles achievable in epithelial lining fluid (ELF) following FDA-approved doses were simulated in the CBR. Treatments were ciprofloxacin at 0.4 g every 8 h as 1-h infusions (80% ELF penetration), meropenem at 6 g/day as a continuous infusion (CI) (30% and 60% ELF penetration), and their combinations. Counts of total and less-susceptible planktonic and biofilm bacteria and MICs were determined. Antibiotic concentrations were quantified by an ultrahigh-performance liquid chromatography photodiode array (UHPLC-PDA) assay. For both strains, all monotherapies failed, with substantial regrowth and resistance of planktonic (≥8 log(10) CFU/ml) and biofilm (>8 log(10) CFU/cm(2)) bacteria at 120 h (MIC(ciprofloxacin), up to 8 mg/liter; MIC(meropenem), up to 64 mg/liter). Both combination treatments demonstrated synergistic bacterial killing of planktonic and biofilm bacteria of both strains from ∼48 h onwards and suppressed regrowth to ≤4 log(10) CFU/ml and ≤6 log(10) CFU/cm(2) at 120 h. Overall, both combination treatments suppressed the amplification of resistance of planktonic bacteria for both strains and of biofilm bacteria for CW44. The combination with meropenem at 60% ELF penetration also suppressed the amplification of resistance of biofilm bacteria for PAOΔmutS. Thus, combination treatment demonstrated synergistic bacterial killing and resistance suppression against difficult-to-treat hypermutable P. aeruginosa strains.